2014
DOI: 10.1002/oby.20751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index, metabolic health and weight change on incident diabetes in a Korean population

Abstract: Objective: The aim of this study was to examine an impact of body mass index (BMI) and weight change on the risk of diabetes according to metabolic health status. Methods: Cohort study of 34,999 Korean men and women 30-59 years of age free of diabetes at baseline were followed-up annually or biennially for an average of 5.1 years. Being metabolically healthy was defined as not having any metabolic syndrome component. Results: During 176,878.6 person-years of follow-up, 889 participants developed diabetes (inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 41 publications
2
28
0
3
Order By: Relevance
“…However, the results of our meta-analysis, through the applied dietary interventions, indicated only significantly beneficial association with the TG concentration within the MHO group. However, the inflammatory status in MHO can be reduced [36], partially stemming from more favorable fatty acid profiles [37] compared to MUHO, a significant decrease in hsCRP concentration was not observed in our analysis. As has been highlighted by Karelis et al [38] health status may strongly influence the response to diet.…”
Section: Discussionmentioning
confidence: 77%
“…However, the results of our meta-analysis, through the applied dietary interventions, indicated only significantly beneficial association with the TG concentration within the MHO group. However, the inflammatory status in MHO can be reduced [36], partially stemming from more favorable fatty acid profiles [37] compared to MUHO, a significant decrease in hsCRP concentration was not observed in our analysis. As has been highlighted by Karelis et al [38] health status may strongly influence the response to diet.…”
Section: Discussionmentioning
confidence: 77%
“…Subjects with obesity who are free of cardiometabolic disease risk factors are termed as having "metabolically healthy obesity" (11,12). However, the existence of the metabolically healthy obesity remains controversial, and it has been debated whether individuals with HO are in fact at lower risk for developing future cardiometabolic disease compared with subjects with equal BMI who are metabolically unhealthy (17)(18)(19)(20)(21)(22). For example, Thomsen and Nordestgaard (18) studied 71,527 individuals from the Copenhagen General Population Study with a median of 3.6 years follow-up and concluded that subjects with obesity, whether or not they had metabolic syndrome, had significantly higher risk for myocardial infarction compared with normal-weight individuals.…”
Section: Cardiometabolic Health In People With Homentioning
confidence: 99%
“…However, there has been an escalating debate (17)(18)(19)(20)(21)(22)(23)(24) disputing whether people with metabolically healthy obesity are indeed at low risk and the degree to which uncomplicated obesity places individuals at risk of cardiometabolic disease. Metabolically healthy obesity in these studies routinely included subjects with risk factors and who, therefore, would predictably be relatively insulin resistant (6) and at higher risk than those lacking all manifestations of cardiometabolic disease (10).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, performing a proper health risk assessment can be a complicated and time-consuming process involving calculations and extrapolations from surveys of detailed health examination items [2]. In order to implement workplace health management in various workplaces, it is helpful to develop a simple, standardized and practical general metabolic health [3,4] risk assessment tool for different worksites. The count (from 0 to 5) of metabolic syndrome (MetS) [5,6] components [7][8][9] have been reported to be associated with a wide-range of risks of unfavorable health outcomes including cardiovascular, cerebrovascular diseases [2,[10][11][12] and several malignancies [13,14], of which the risks rise in proportion to the count of MetS components.…”
Section: Introductionmentioning
confidence: 99%